Open innovation and prizes: Is the European Commission really committed? - Isabelle Liotard; Valérie Revest (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2021)
In 2015, the European Commission decided upon new political directions toward open innovation. Our aim is to assess to which extend the European Innovation Prizes are enshrined in the open innovation's movement. 22 innovation's prizes have been scrutinized on the basis on official EC's documents and interviews carried out with stakholders. The results tend to show that if a degree of openess is noted, European Innovation prizes could tend toward greater citizens' inclusivity. From an academic viewpoint, we propose to combine the properties of the concepts of innovation prizes and communities.
Keywords: O32; O36; O33; 330; Prize; Open Innovation; European Commission; Public Policy; Crowdsourcing; Stakeholders